Management Guidelines to Increase the Performance of Railway Construction Workers in Thailand - Savangprom, Apisit; Tailangka, Wanwipha; Janma, Chaiwut (Arts of Management Journal, 2024)
The objectives of this research were to: 1) study the conditions and problems of the competency of workers in railway construction in Thailand; 2) study the competency of workers in railway construction in Thailand; 3) compare the differences between the competency of workers in railway construction in Thailand classified by organizational characteristics factors; 4) study the factors affecting the competency of workers in railway construction in Thailand; and 5) present the guidelines for management to enhance the competency of workers in railway construction in Thailand. The sample group included the supervisory managers of railway construction contractors in Thailand, a total of 400 people, and key informants that consisted of academics and railway construction labor administrators, a total of 19 people. Data were analyzed using descriptive statistics, one-way ANOVA, and MRA. The results found that 1. the railway system has a shortage of workers with specific skills in railway work, both quantitatively and qualitatively. 2. The workers overall performance is at a high level., it was found that there is labor development. Overall, it is at a high level, and it has a high level of labor management to a large extent as well. 3. Workers in belonging to companies with experience in rail work and companies that have organized their own railway training programs in the past five years have different opinions about their ability to work in railway construction. Significantly at the .01 and .05 levels. 4. All labor development factors are able to jointly explain the competency of railway construction workers at 50.90 percent and every labor management factor, together, can explain the competency of railway construction workers at 34.30 percent. and 5. The guidelines for management to increase the performance of railway construction workers includes organizing training in specific skills and networking with entrepreneurs.